Incidence and risk factors for bone metastases at presentation in solid tumors - Knapp, Brendan J.; Cittolin-Santos, Giordano F.; Flanagan, Mary E.; Grandhi, Nikhil; Gao, Feng; Samson, Pamela P.; Govindan, Ramaswamy; Morgensztern, Daniel (Frontiers in Oncology, 2024)
Introduction: Bone metastases are associated with increased morbidity and decreased quality of life in patients with solid tumors. Identifying patients at increased risk of bone metastases at diagnosis could lead to earlier interventions. We sought to retrospectively identify the incidence and predictive factors for bone metastases at initial diagnosis in a large population-based dataset.Methods: The Surveillance, Epidemiology, and End Results (SEER) database was used to identify patients 18 years-old or older diagnosed with solid cancers from 2010 to 2019. Patients with hematologic malignancies and primary tumors of the bone were excluded. We calculated the incidence and predictive factors for bone metastases according to demographic and tumor characteristics.Results: Among 1,132,154 patients identified, 1,075,070 (95.0%) had known bone metastasis status and were eligible for the study. Bone metastases were detected in 55,903 patients (5.2% of those with known bone metastases status). Among patients with bone metastases, the most common primary tumors arose from lung (44.4%), prostate (19.3%), breast (12.3%), kidney (4.0%), and colon (2.2%). Bone metastases at presentation were most common in small cell lung cancer (25.2%), non-small cell lung cancer (18.0%), and esophageal adenocarcinoma (9.4%). In addition to stage classification, predictors for bone metastases included Gleason score (OR 95.7 (95% CI 73.1 -125.4) for Grade Group 5 vs 1 and OR 42.6 (95% CI 32.3 -55.9) for Group 4 vs 1) and PSA (OR 14.2 (95% CI 12.6 -16.0) for PSA > 97 vs 0 -9.9) for prostate cancer, HER2 and hormonal receptor (HR) status (OR 2.2 (95% CI 1.9 -2.6) for HR+/HER2+ vs HR-/HER2-) for breast cancer, histology (OR 2.5 (95% CI 2.3 -2.6) for adenocarcinoma vs squamous) for lung cancer, and rectal primary (OR 1.2 (95% 1.1 -1.4) vs colon primary) and liver metastases (OR 8.6 (95% CI 7.3 -10.0) vs no liver metastases) for colorectal tumors.Conclusions: Bone metastases at presentation are commonly seen in solid tumors, particularly lung, prostate, breast, and kidney cancers. Clinical and pathologic factors are associated with a significantly increased risk for bone metastases.